Digital transformation a new challenge for higher education: A curriculum proposal - Moreira, Fernando (2018)
The world in general and the organizations in particular are changing faster than ever. Mobility, cloud computing, big data, and social media, the pillars of Digital Transformation (DT) are driving organizations to the next level of digital customer engagement and IT-enabled business processes, products, and services. In almost all organizations, digital technologies are bringing about unprecedented transformation and changing the work and lives of the people in ways that have never anticipated. In this context, the teaching of Digital Transformation both at the higher level and training education must be urgently aligned with these transformations, so that present and future professionals of computation and business may learn to solve problems with greater agility. Such agility is also required to organizations. In this paper a curriculum of a Digital Transformation course at the High Education level is proposed in order to address the new challenges of Digital Transformation in organizations.